Heavy metal level assessment in canned fish / Muhammad Aisamuddin Ahmad - Ahmad, Muhammad Aisamuddin (Faculty of Applied Sciences, 2017)
Heavy metal (Zn, Cu, Pb and Cd) concentration of canned sardine and canned mackerel, commercialized in Malaysia were determined using Flame Atomic Analyzer Spectroscopy (FAAS). The average contents of heavy metals in canned sardine and canned mackerel were found as 0.264 and 0.222 mg/kg for zinc, 0.0454 and 0.0505 mg/kg for copper, BDL for lead and 0.0305 and 0.0096 mg/kg for cadmium, respectively. All these products have below permissible limit of heavy metals allowed by the Malaysian Food Regulation 1985 and pose no risk with respect to the human health since the Hazard Index (HI) was below unity. Long term monitoring of heavy metals in canned fish are needed to prevent any potential health risks.